Comments on "Essential work of fracture analysis for surface modified carbon fiber/polypropylene composites with different interfacial adhesion" [Polymer Composites 41 (9) (2020): 3541–3551]. Issue 3 (28th December 2021) - Rajaee, Pouya; Ashenai Ghasemi, Faramarz; Fasihi, Mohammad
Abstract: In this paper, some comments on the study "Essential work of fracture analysis for surface modified carbon fiber/polypropylene composites with different interfacial adhesion" Polymer Composites 41 (9) (2020): 3541–3551, have been discussed. The comments are mostly concentrated on the technique utilized for the assessment of the parameters of fracture toughness. The essential work of fracture (EWF) approach was employed for all the samples to characterize the fracture manner, while it appears that some of the samples did not meet the prerequisites of the EWF method. These prerequisites are as follows: the ligament length must be completely yielded before the onset of crack propagation, self‐similarity between load–displacement curves is a requirement, and fracture must occur under plane stress conditions. Therefore, the information, data, and results obtained by the authors are questionable. Abstract :